Bilevel approach for optimal location and contract pricing of distributed generation in radial distribution systems using mixed-integer linear programming - Rider, Marcos J. [UNESP]; López-Lezama, Jesús María; Contreras, Javier; Padilha-Feltrin, Antonio [UNESP] (Institution of Engineering and Technology (IET), 2013)
In this study, a novel approach for the optimal location and contract pricing of distributed generation (DG) is presented. Such an approach is designed for a market environment in which the distribution company (DisCo) can buy energy either from the wholesale energy market or from the DG units within its network. The location and contract pricing of DG is determined by the interaction between the DisCo and the owner of the distributed generators. The DisCo intends to minimise the payments incurred in meeting the expected demand, whereas the owner of the DG intends to maximise the profits obtained from the energy sold to the DisCo. This two-agent relationship is modelled in a bilevel scheme. The upper-level optimisation is for determining the allocation and contract prices of the DG units, whereas the lower-level optimisation is for modelling the reaction of the DisCo. The bilevel programming problem is turned into an equivalent single-level mixed-integer linear optimisation problem using duality properties, which is then solved using commercially available software. Results show the robustness and efficiency of the proposed model compared with other existing models. As regards to contract pricing, the proposed approach allowed to find better solutions than those reported in previous works. © The Institution of Engineering and Technology 2013.
Keywords: Bi-level approaches; Bilevel programming problem; Distributed generators; Distribution companies; Mixed integer linear programming; Optimisation problems; Radial distribution systems; Wholesale energy market; Commerce; Distributed power generation; Linear programming; Location; Optimization; Costs